Impact of wood fuel consumption on forest degradation, health outcomes and economic growth in Sub-Saharan Africa - Sulaiman, Chindo (2017)
This thesis is motivated based on the increasing production of wood fuel driven by its growing consumption in the Sub-Saharan African region. While other parts of the world are already on the verge of reducing the use of wood fuel and switching to much cleaner and healthier fuel such as electricity, considering the potential environmental, health and economic effects it has, the story is different in Sub-Saharan Africa. The demand for the wood fuel in Sub-Saharan Africa is on the increase and has been even projected to increase further in the coming decades. This calls for concern and research into the area, as some challenges accompany the increase. These likely challenges, which are related to forest degradation, health and economic growth, are the focus of our study. Therefore, this study specifically investigates the impact of wood fuel consumption on forest degradation as objective one. Whereas, the impact of wood fuel consumption on health outcomes (under five and adult mortality rates) and economic growth are investigated as objective two and three, respectively. The organisation of this thesis is based on essay format of thesis layout and not the conventional format. A panel method of system generalized method of moment (GMM) was used to estimate the impact of wood fuel consumption on forest degradation and the impact of wood fuel consumption on health outcomes in 45 and 46 sub-Saharan African countries, respectively, for the 2005-2013 period. While the impact of wood fuel consumption on economic growth was estimated using panel autoregressive distributed lag (ARDL) method, which included pooled mean group, mean group and dynamic fixed effect estimators in 19 sub-Saharan African countries for the 1979-2013 period. The data on all the variables for all the countries were sourced from the databases of World development indicators (WDI) of World Bank, World Governance Indicators (WGI), and food and agricultural organisation (FAO). The estimated results for the impact of wood fuel consumption on forest degradation reveal that wood fuel consumption significantly increases forest degradation in the region. When interacted with control of corruption or government effectiveness, wood fuel consumption has been found to have a negative impact on forest degradation. It suggests that a sound control of corrupt practices and effective governance can help to reduce degradation in the region. On the impact of wood fuel consumption on health outcomes, the results show that wood fuel consumption has significant positive impact on adult and under-five mortality rates in the region. This finding confirms the assertion that the rising deaths recorded in the region from indoor air pollution related illnesses can be linked to wood fuel smoke. Lastly, the results of the impact of wood fuel consumption on economic growth disclose that wood fuel consumption causes a decline in economic growth through a decrease in productivity of labour and increasing medical expenses due to indoor air pollution related infections. The estimated models were validated via diagnostic and robustness tests, which suggest that the estimates were reliable. The general findings indicate that an increase in wood fuel consumption facilitates forest degradation, adult and under-five mortality rates, as well as slow down economic growth. The policy recommendation from this study is that governments of Sub-Saharan African countries should strengthen the fight against corruption and ensure effective governance, as well as strive to make the modern fuel available and affordable. Thus, it will assist in reducing the too much dependence on wood sources for energy use. Consequently, the region can safeguard its forests, prevent indoor air related smoke diseases, and avert the adverse effect of wood fuel consumption on growth.